The Effect of Service Quality and Endorser Credibility on Purchase Decision Mediated By Brand Image (Empirical Study: Active Students of Jaya Buana Vocational High School in Tangerang Regency) - Jamaludin Jamaludin; Liem Bambang Sugiyanto (Return : Study of Management, Economic and Bussines, 2024)
This study examines the impact of service quality and endorser credibility on the purchase decisions of prospective students at SMK Jaya Buana, a vocational high school in Tangerang Regency, with brand image as a mediating factor. The research employs a comprehensive design that includes validity, reliability, and hypothesis testing, using structural equation modeling (SEM) to analyze the data. The findings reveal that both service quality and endorser credibility significantly influence purchase decisions, with service quality identified as the most critical contributor. Furthermore, the study demonstrates that brand image plays a vital role in enhancing the effect of these variables on purchase decisions, acting as a powerful mediator. The results suggest that improving service quality and leveraging credible endorsers can significantly boost a school's brand image, thereby increasing student enrollment. This research underscores the importance of strategic management in educational institutions to attract more students by focusing on service excellence, credible endorsements, and a strong brand image.